2023
DOI: 10.1097/md.0000000000034517
|View full text |Cite
|
Sign up to set email alerts
|

Transversus abdominis plane block versus local anesthetic infiltration for anesthetic effect in peritoneal dialysis catheter insertion: A systematic review and meta-analysis

Abstract: Background: The transversus abdominis plane (TAP) block is commonly used in surgical practice for postoperative analgesia in abdominal surgery. However, numerous studies have demonstrated that TAP block is also suitable for intraoperative anesthesia of peritoneal dialysis catheter (PDC) insertion, although its efficacy and safety are still controversial. Local anesthetic infiltration (LAI) is currently the most general anesthesia strategy for PDC insertion. Consequently, we conducted this systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…conducted a systematic review of the anesthetic and analgesic effects of regional blockade and local anesthesia during the placement of a PD catheter and revealed that regional anesthesia may be superior to local anesthesia. However, they did not focus on the relationship between drug dosage and adverse reactions [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…conducted a systematic review of the anesthetic and analgesic effects of regional blockade and local anesthesia during the placement of a PD catheter and revealed that regional anesthesia may be superior to local anesthesia. However, they did not focus on the relationship between drug dosage and adverse reactions [ 14 ].…”
Section: Discussionmentioning
confidence: 99%